(untitled) (Research, Society and Development, 2022)
Obesity is a chronic disorder of multifactorial origin (neuroendocrine, psychic, intestinal and genetic factors) that results from a metabolic-energetic imbalance, whereby a long-term excess of energy intake over expenditure leads to accumulation in the form of fat. The control of the energy balance is carried out by the central nervous system by means of necessary neuroendocrines, in which peripheral circulating hormones, such as leptin and insulin, signal specialized neurons of the hypothalamus over the body’s fat stores and induce adequate responses for the maintenance of stocks god stability. Thus, the positive energy balance for a long period, determined by macronutrient intake, energy expenditure and thermogenesis, will result in body weight gain in the form of fat, while the negative energy balance will result in no opposite effect. In this systematic review of works published between 2008 and 2021, neuroendocrine mechanisms that control hunger and satiety, and their relationship with obesity, will be discussed. Thus evidencing that this regulation is carried out by a complex mechanism that needs to be very well understood in order to treat or even prevent obesity.